2005
DOI: 10.1007/s00167-005-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-bundle, four-tunnel anterior cruciate ligament reconstruction

Abstract: We reviewed 33 patients who underwent anterior cruciate ligament (ACL) reconstruction using a two-bundle, four-tunnel technique. The posterolateral bundle (PLB) and anteromedial bundle (AMB) were individually reconstructed with gracilis and semitendinosus tendon auto-grafts, respectively, using separate tibial and femoral tunnels. At final follow-up (24 months post surgery, range 18-31) the International Knee Documentation Committee's (IKDC) objective final evaluation scores were 69 A, 19 B, 12% C. The mean gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 30 publications
(51 reference statements)
1
49
1
5
Order By: Relevance
“…The failure rate ranged from 0% to 3% in 7 studies, 7,10,17,19,20,25,26 from 4% to 6% in 6 studies, 9,11,12,21,22,27 from 7% to 10% in 4 studies, [13][14][15][16] and from 14% to 24% in 4 studies. 8,18,23,24 Fourteen studies [7][8][9][10][11][14][15][16][17][18][19][20]23,26 (67%) reported no injuries in the contralateral ACL, but in the other 7 studies, 12,13,21,22,24,25,27 the rates of contralateral ACL injuries ranged from 2% to 15%.…”
Section: Resultsmentioning
confidence: 97%
“…The failure rate ranged from 0% to 3% in 7 studies, 7,10,17,19,20,25,26 from 4% to 6% in 6 studies, 9,11,12,21,22,27 from 7% to 10% in 4 studies, [13][14][15][16] and from 14% to 24% in 4 studies. 8,18,23,24 Fourteen studies [7][8][9][10][11][14][15][16][17][18][19][20]23,26 (67%) reported no injuries in the contralateral ACL, but in the other 7 studies, 12,13,21,22,24,25,27 the rates of contralateral ACL injuries ranged from 2% to 15%.…”
Section: Resultsmentioning
confidence: 97%
“…Muneta et al (1999; 54 DBT) could point out a trend in improved anterior stability with the DBT, compared with earlier results with SBT from the same surgeon. Colombet et al (2006; 33 DBT) demonstrated that results with DBT are at least equivalent to those with SBT and showed an apparent trend toward improved control of anterior laxity.…”
Section: Resultsmentioning
confidence: 99%
“…17,18,40 The reciprocal function between the 2 bundles has been a rationale for tensioning strategies of grafts in double-bundle ACL reconstructions. 10,45 However, some recent studies could not confirm the reciprocal function between the AM and PL bundles. 21,35,43 Jordan et al 21 found that the AM and PL bundles of ACL played a more important role in low flexion angles, with the 2 bundles reaching maximum length near extension and reducing length with flexion during weightbearing knee flexion.…”
Section: Discussionmentioning
confidence: 98%